Studi Bahan Ajar Tentang Sejarah Islam di Indonesia dalam Buku Ajar Sejarah Nasional Indonesia Tingkat SMA/ MA dalam Perspektif Pendidikan Islam - Dahamnuri, Moh.; Husaini, Adian; Saefuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2016)
The focus of this study is about the materials of History of Islam in Indonesia on Indonesian National History Textbook in the Perspective of Islamic Education. It’s not only knowing of this materials but also can be useful for people who want to master of historical of Islam in Indonesia. In the process of learning the teacher presenting the material, starting with the creation of teaching materials interesting and innovative. Teaching materials have great contribution for the success of the learning process. In this occasion the role of the teacher as a facilitator is very important because it also as a resource in teaching and learning. Learning based on the students-oriented could be possible to learn from a variety of sources of information independently, both of graphic media such as books, magazines, newspapers, newsletters, and others; or on electronic media such as radio, television, film slides, video, computer, or perhaps from the internet. Writing the past of historical of human life is strongly influenced by the ideology of the author, also at the time who was in the power in that country. So that it is presented to be criticize on its truth do not accept what if it were going to leave uncertainty forever. The method is used in this research is descriptive narrative, that research on describing what the data that the author has found from many sources that are the subject of a study of the Qur’an, Hadith, and scholarly opinion which strengthens. While the theory is used in this case is theories have Framing in content analysis. Framing analysis is used to determine how the reality framed by the media. Through analysis of the framing will be known who controls whom, who opposed the who, where friends where the opponent, where the patron and which clien. At the high school level (high school) or Madrasah Aliyah (MA) History teaching aims to encourage pupils can critical thinking, analysis and synthesis. Understanding the past life to be used as the foundation of life of the present and future. Also understand that history is a part of everyday life. The observation of the author after reading the teaching material for the National History Indonesia SMA / MA, there are theories that led to the materialist sourced from Western secular theory. The next presentation of teaching materials national history in SMA / MA when viewed from the perspective of Islamic education efforts are needed to Islamization include Islamization of Sciences, the Islamization of writing and teaching history, because history, as well as other science today predominantly influenced by the theories of secularism which considers a value-free and not nothing to do with religion; especially the Islamic religion that comes from revelation of Allah (Qur’an) and hadiths of The Messenger of Allah SAW. The teachers that administer the National History Lesson is expected to exploit the opportunities available that actively attending activities Subject Teachers Council (MGMP) to formulate, discuss and criticize the teaching materials that have been available in the Handbook both for teachers and for students. Of these activities are expected to grow curiosity continuously so that the teachers are always seeking to prepare themselves before teaching in the classroom. Likewise, students are stimulated to seek his own experiences with the task given of their selves both structured and unstructured task. Hopely the students can take advantage of opportunities for critical thinking in viewing and studying the teaching materials are available that they can eventually finds himself to be used as provision of his life in the future. Keyworld: teaching material, history of Islam, islamic education